Insights into distinct biocarbon assembly and graphitization derived from large-scale bioresource by integrating machine learning with Raman and XRD spectroscopic profiling - Junsheng Yu; Jing Hong; Yujia Fang; Jiacheng Kang; Zongtai Tang; Lei Zhu; Bing Gao; Ling Luo; Dan Sun; Yanting Wang; Liangcai Peng; Hua Yu (Bioresource Technology, 2026)

Amphiregulin as a central dynamic network biomarker in inhaled polyhexamethylene guanidine triggered pulmonary fibrosis - Jianzhong Zhang; Xin Li; Yuxin Ma; Wanjun Zhang; Zihao Han; Yanting Li; Jiayin Sun; Siqi Wang; Wei Han; Jing Liu; Yuxin Zheng; Jinglong Tang (Journal of Hazardous Materials, 2026)

Preparation and characterization of chitosan‑sodium alginate complex edible casings incorporated with tea polyphenols and their application in dry-cured sausages - Huanhuan Li; Yanting Gao; Teng Xu; Ke Zhao; Mingwei Su; Jun He; Honggang Tang (Food Chemistry, 2026)

Regulatory mechanisms of spatiotemporal variations in aboveground and belowground net primary production in global terrestrial ecosystems - Tao Zhou; Yanting Xiong; Zhihan Yang; Yuting Hou; Yuqing Zhang; Dan Liao; Xiaodong Wang; Dinghui Xu; Pingfeng Li; Peng Hou; Wenji Zhao; Guo Chen; et al. (Agricultural and Forest Meteorology, 2026)

Stabilizing photogranule systems under low-light and limited-aeration: From operational strategy to underlying mechanism - Xiaojing Yang; Lan Tang; Jinke Sun; Fahui Ji; Peng Qi; Meng Yan; Yanjuan Luo; Chen Yang; Yanting Lin; Hui Lu (Water Research, 2026)

Diesel exhaust induces hepatic steatosis by activating the aryl hydrocarbon receptor/CD36 pathway - Qian Song; Xueying Zhang; Yanting Li; Zixuan Liang; Ao Han; Xiaoran Wei; Xiaowen Tang; Juntong Wei; Wei Han; Shanfa Yu; Hongna Zhang; Yuxin Zheng (Journal of Hazardous Materials, 2026)

Combustion and explosion reaction kinetics of thermal runaway gases from three lithium-ion batteries with different metal-oxide cathodes - Song Lin; Yanting Cao; Yunhao Li; Kai Zheng; Yan Tang; Juncheng Jiang (Fuel, 2026)

Transcription factor CsWRKY76 potentially involved in accumulation of scoparone and pentamethoxyflavone in citrus fruit stimulated by salicylic acid - Shuqing Xu; Shuzhen Yang; Yanting Yang; Meihong Zhang; Anqi Tang; Yi Li; Litao Peng (Postharvest Biology and Technology, 2025)

Problem analysis and new scheme design for AB-BNCT solid Li targets - Kaiwen Qin; Nailiang Zhuang; Xijun Zhao; Yanting Zhang; Hangbin Zhao; Xiaobin Tang (Annals of Nuclear Energy, 2025)

Visualization of mitochondrial molecular dynamics during mitophagy process by label-free surface-enhanced Raman scattering spectroscopy - Hailan Jia; Chi Wang; Yan Fu; Yalin Wang; Xiaoyu Zhang; Yuezhou Tang; Jiahao Ding; Kun He; Jing Wang; Yanting Shen (Analytica Chimica Acta, 2025)

Insights into contrastive cellulose nanofibrils assembly and nanocrystals catalysis from dual regulations of plant cell walls - Yuanhang Ai; Hailang Wang; Peng Liu; Hua Yu; Mengdan Sun; Ran Zhang; Jingfeng Tang; Yanting Wang; Shengqiu Feng; Liangcai Peng (Science Bulletin, 2024)

Mechanism underlying the role of integrin α3β1 in adhesive dysfunction between thyroid cells induced by diesel engine exhaust particles - Xiaoyin Guo; Siying Tang; Yanting Li; Chaohui Mu; Hongna Zhang; Qixiao Jiang; Menghui Jiang; Wei Han; Yuxin Zheng; Jinmei Piao (Science of The Total Environment, 2024)

Polydopamine-assisted minute fabrication of vertically aligned ZIF-L membranes for CO2/N2 separations - Keming Zhang; Sihui Li; Xiaohe Tian; Rui Zhang; Xiaoting Feng; Qingnan Wang; Yanting Tang; Chenlu Liu; Hongxia Gao; Shaofei Wang (Chemical Engineering Journal, 2024)

Spectrum detection and analysis of the epidemiological characteristics of infectious pathogens in the feline respiratory tract - Houbin Ju; Dequan Yang; Jizexiao Jin; Jian Wang; Xin Li; Xianchao Yang; Jie Ge; Jiuchao Zhu; Haixiao Shen; Jun Lu; Xiujuan Wu; Xiaoxu Wang; et al. (Archives of Virology, 2024)

Diesel exhaust exposure induced squamous metaplasia of corneal epithelium via yes-associated protein activation - Xiaoya Ji; Yanting Li; Meike Liu; Linfei Chen; Xinglin Zhang; Mingyue Wang; Shuhan Tian; Lin Lu; Mingliang Zhang; Yuxin Zheng; Jinglong Tang (Chemosphere, 2024)

Cationic cellulose nanofiber solid electrolytes: A pathway to high lithium-ion migration and polysulfide adsorption for lithium-sulfur batteries - Chenhao Ji; Shuanglin Wu; Feng Tang; Yanting Yu; Fenglin Hung; Qufu Wei (Carbohydrate Polymers, 2024)

Nutrient enrichment driven by canopy rainfall redistribution: Mechanism, quantification, and pattern - Chuan Yuan; Xiaoping Yue; Yafeng Zhang; Yu Zhang; Yanting Hu; Qiang Tang; Li Guo; Shuai Wang; Xingwu Duan; Wenhua Xiang; Xiaohua Wei; Xiaoyan Li (Science China Earth Sciences, 2024)

ZIF-8 Gel/PIM-1 mixed matrix membranes for enhanced H2/CH4 separations - Keming Zhang; Xianye Luo; Sihui Li; Xiaohe Tian; Qingnan Wang; Chenlu Liu; Yanting Tang; Xiaoting Feng; Rui Zhang; Shuangfeng Yin; Shaofei Wang (Chemical Engineering Journal, 2024)

Preparation of serpentine fiber/poly (vinyl alcohol) aerogel with high compressive strength to stabilize phase change materials for thermal energy storage - Xiaochao Zuo; Xinyi Zhang; Yili Tang; Yanting Zhang; Xu Li; Huaming Yang (Applied Clay Science, 2024)

Boron doping g-C3N4 supported Cu2O for photocatalytic reforming of xylose into lactic acid - Yanting Lv; Weiyong Shao; Yuling Kong; Nanhua Li; Xinrui Huang; Zhihao Tang; Murong Gong; Lizi Li; Weiqi Wei (Journal of Environmental Chemical Engineering, 2023)

MPA-capped CdTequantum dots induces endoplasmic reticulum stress-mediated autophagy and apoptosis through generation of reactive oxygen species in human liver normal cell and liver tumor cell - Ting Zhang; Jie Lu; Ying Yao; Yanting Pang; Xiaomeng Ding; Meng Tang (Environmental Pollution, 2023)

BsEXLX of engineered Trichoderma reesei strain as dual-active expansin to boost cellulases secretion for synergistic enhancement of biomass enzymatic saccharification in corn and Miscanthus straws - Chengbao Xu; Tao Xia; Hao Peng; Peng Liu; Yihong Wang; Yanting Wang; Heng Kang; Jingfeng Tang; Muhammad Nauman Aftab; Liangcai Peng (Bioresource Technology, 2023)

Characterization of two-component system CitB family in Salmonella enterica serovar Gallinarum biovar Gallinarum - Jiaqi Chen; Xiao Zhou; Yanting Tang; Zhijie Jiang; Xiamei Kang; Jianfeng Wang; Min Yue (Veterinary Microbiology, 2023)

Genomic characterization of ESBL-producing Salmonella Thompson isolates harboring mcr-9 from dead chick embryos in China - Mohammed Elbediwi; Yanting Tang; Min Yue (Veterinary Microbiology, 2023)

An epipolythiodioxopiperazine alkaloid and diversified aromatic polyketides with cytotoxicity from the Beibu Gulf coral-derived fungus Emericella nidulans GXIMD 02509 - Miaoping Lin; Zhenzhou Tang; Jiaxi Wang; Humu Lu; Chenwei Wang; Yanting Zhang; Xinming Liu; Chenghai Gao; Yonghong Liu; Xiaowei Luo (Journal of Zhejiang University-SCIENCE B, 2023)

Ex vivo coronary endothelial cell activation associated with indoor coal combustion initiated atherosclerosis - Wanjun Zhang; Yaxian Pang; Wenting Cheng; Tao Wang; Yanting Li; Xin Li; Jianzhong Zhang; Xiaowen Xia; Yuxin Zheng; Rong Zhang; Jinglong Tang (Science of The Total Environment, 2023)

Construction of PP membranes with robust interfacial stability by ALD and fluorinated grafting for high salt solution distillation - Lei Zhang; Dan He; Jia Li; Yanting Li; Yiming Xiao; Jun Xiang; Wei Du; Na Tang (Desalination, 2023)

Intermittent ultrasound retains cellulases unlock for enhanced cellulosic ethanol with high-porosity biochar for dye adsorption using desirable rice mutant straw - Zhen Hu; Qian Li; Yuanyuan Chen; Tianqi Li; Youmei Wang; Ran Zhang; Hao Peng; Hailang Wang; Yanting Wang; Jingfeng Tang; Muhammad Nauman Aftab; Liangcai Peng (Bioresource Technology, 2023)

Vitamin D deficiency leads to the abnormal activation of the complement system - Huan Li; Xiaomin Xie; Guirong Bai; Dan Qiang; Li Zhang; Huili Liu; Yanting He; Yanpan Tang; Ling Li (Immunologic Research, 2023)
Vitamin D deficiency can damage the human immune system, and the complement system is a key component of the immune system. This study aimed to elucidate the mechanism by which vitamin D affects the immune system by analyzing the changes in the protein expression of the complement system under different vitamin D levels. We selected 40 participants and divided them into three groups according to their serum levels of 25-hydroxyvitamin D (25(OH)VD): group A, 25(OH)VD ≥ 40 ng/mL; group B, 30 ng/mL ≤ 25(OH)VD < 40 ng/mL; and group C, 25(OH)VD < 30 ng/mL. Serum samples were subjected to biochemical analysis, followed by proteomic analysis using high-throughput untargeted proteomic techniques. Vitamin D deficiency increased the levels of fasting blood sugar, fasting serum insulin, and homeostasis model assessment (HOMA) of insulin resistance and decreased the secretion of HOMA of β-cell function, which led to insulin resistance and glucose metabolism disorder. Moreover, vitamin D deficiency resulted in the abnormal expression of 56 differential proteins, among which the expression levels of complement factor B, complement component C9, inducible co-stimulator ligand, and peptidase inhibitor 16 significantly changed with the decrease in vitamin D content. Functional enrichment analysis of these differential proteins showed that they were mainly concentrated in functions and pathways related to insulin secretion and inflammation. In conclusion, vitamin D deficiency not only contributes to insulin resistance and glucose metabolism disorder but also causes abnormal protein expression, resulting in the abnormal activation of the complement system. This study provides a novel theoretical basis for further studies on the relationship between vitamin D and the immune system.

Incomplete genome doubling enables to consistently enhance plant growth for maximum biomass production by altering multiple transcript co-expression networks in potato - Kanglu Zhao; Nengzhou Jin; Meysam Madadi; Youmei Wang; Lei Wu; Zhijun Xu; Jinxuan Wang; Jing Dong; Shang-wen Tang; Yanting Wang; Liangcai Peng; Zhiyong Xiong (Theoretical and Applied Genetics, 2022)

Unraveling Physiological and Metabolomic Responses Involved in Phlox subulata L. Tolerance to Drought Stress - Yan Xiong; Yanting Qu; Hui Han; Fei Chen; Li Li; Huanwei Tang; Daidi Che; Xing Zhang (Plant Molecular Biology Reporter, 2021)

High expression of long non-coding RNA Linc-A associates with poor survival in patients with colorectal cancer - Chong Zhao; Can Gan; Yang Xiao; Rui Liu; Linhao Zhang; Tian Lan; Yanting Ye; Huan Tong; Zhiyin Huang; Chengwei Tang; Jinhang Gao (Molecular Biology Reports, 2020)

Cotton CSLD3 restores cell elongation and cell wall integrity mainly by enhancing primary cellulose production in the Arabidopsis cesa6 mutant - Huizhen Hu; Ran Zhang; Yiwei Tang; Chenglang Peng; Leiming Wu; Shengqiu Feng; Peng Chen; Yanting Wang; Xuezhu Du; Liangcai Peng (Plant Molecular Biology, 2019)

CRISPR/Cas9-mediated gene editing in human zygotes using Cas9 protein - Lichun Tang; Yanting Zeng; Hongzi Du; Mengmeng Gong; Jin Peng; Buxi Zhang; Ming Lei; Fang Zhao; Weihua Wang; Xiaowei Li; Jianqiao Liu (Molecular Genetics and Genomics, 2017)

Ecological indicators showing the succession of macrofauna communities in Sonneratia apetala artificial mangrove wetlands on Qi’ao Island at Zhuhai, South China - Yijie Tang; Zhanqiang Fang; Zaiwang Zhang; Yanting Zhong; Kang Chen; Benhan Liu; Junjie Fan; Tiantian Xiong; Xiaosheng Lu (Acta Oceanologica Sinica, 2014)

Ecological influence of exotic plants of Sonneratia apetala on understory macrofauna - Yijie Tang; Zhanqiang Fang; Kang Chen; Zaiwang Zhang; Yanting Zhong; Dong An; Xiongbang Yang; Baowen Liao (Acta Oceanologica Sinica, 2012)